2020
DOI: 10.1111/ijfs.14753
|View full text |Cite
|
Sign up to set email alerts
|

The use of pullulan coatings with propolis extract to extend the shelf life of blueberry (Vaccinium corymbosum) fruit

Abstract: Consuming fresh blueberries has many health benefits due to the extremely high level of phytonutrients. During storage, the berries spoil due to microbial contamination. The aim of the work was to investigate the effect of pullulan coating containing 5% and 10% propolis extract on reducing the number of bacteria and mould and on the physicochemical properties of coated blueberries during storage. The results showed that the count of microorganisms was reduced by 3–4.5 logarithmic cycle after 21 days (16°C, RH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 38 publications
4
24
0
1
Order By: Relevance
“…Raw propolis cannot be used directly as a raw material due to its high content of pollutants, which mainly consists of waxes and resins [ 32 ]. Therefore, it is necessary to extract polar and non-polar active components of propolis using an appropriate solvent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Raw propolis cannot be used directly as a raw material due to its high content of pollutants, which mainly consists of waxes and resins [ 32 ]. Therefore, it is necessary to extract polar and non-polar active components of propolis using an appropriate solvent.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies demonstrated significant antioxidant activity when chitosan was used as a base polymer, both in pork loins [ 61 ] and in ready-to-cook meat products [ 62 ]. Additionally, significant antioxidant activity was demonstrated when PE was used in meat and fish products [ 23 , 32 ]. The negligible antioxidative effect of PE observed in the current study might be due to the low concentration of the bioactives present in the pork samples that conferred a minimal protective effect against lipid oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of edible films and coating can contribute to delaying the microbiological damage of fruit. Additionally, the addition of polyphenolic compounds considerably improves the antifungal potential of the formulations [32,36].…”
Section: Antifungal Activity In Vitromentioning
confidence: 99%
“…The use of pullulan coatings, an exopolysaccharide produced by the fungus Aureobasidium pullulans, combined with propolis extract reduced the population of bacteria and moulds by 3-4.5 log in fresh blueberries stored at 16 • C for 21 days. In addition, these coatings contributed to the delay in the ripening of blueberries and the decrease in water loss [136]. The application of allyl isothiocyanate, a natural compound present in plants of the Cruciferae family, reduced blueberry decomposition during storage at 10 • C for 21 days, which was associated with the generation of reactive oxygen species.…”
Section: Biological Strategiesmentioning
confidence: 99%